Successful client-consultant - Naidoo, Vivien (My University, 2011)
The activity of management consultants continues to increase in South Africa (SA). South African public and private sector clients continue to increase their spend on consulting services. South African clients are however relatively less mature consumers of management consulting services when compared to their counterparts in the United States (US) and the United Kingdon (UK). This fact, together with the complexity and uniqueness of the South African political and business landscapes, renders the impact of local conditions on consulting engagements more significant. The purpose of this research has been to investigate the factors for successful client-consultant engagements in the South African context. The research was undertaken from the client perspective and included a sample of SA clients and UK clients. A comparison was made between the responses of SA clients and UK clients to highlight aspects that appeared specific to the SA context. From the literature review six common factors namely (1) consultant skill, (2) consultant innovation, (3) communication, (4) relationship, (5) project delivery and (6) cost were reviewed. Data was collected from clients’ ratings of past consulting engagements of a management consulting firm headquartered in the UK with a local office in SA. A sample of 38 consulting engagements in SA and 35 UK engagements was used. Through regression analysis it was found that consultant skill, communication and relationship were significant factors for consulting engagement success in South Africa. SA clients were, however, less likely to evaluate the success of the engagements based on cost, consultant innovation and project delivery. Comparatively project delivery and communication was significant for clients in the UK, while consultant skill, relationship, consultant innovation and cost were less significant in evaluation of success. This research has important implications for consulting firms – especially foreignbased firms – in terms of their consulting approaches in South Africa. This helps such firms better understand the needs of SA clients in consulting engagements, thereby increasing the chances of success.
MBA - WBS
Keywords: Consultants, South Africa; Management consultants